The Effects of Perceptual Congruence and Sex on Subordinates' Performance Appraisals of Their Managers - Wexley, Kenneth N.; Pulakos, Elaine D. (Academy of Management Journal, 1983)
In an investigation of the relationship between subordinates' perceptual congruence (SPC) and sex on subordinates' performance appraisals of their immediate managers, SPC was found to be significantly related to subordinate evaluations of their managers within particular manager-subordinate sex combinations. These results are explained in terms of reinforcement theory and the role episode model.